Investigation of Temperature, Thermodynamic Parameters and Dielectrical Properties of Poly(vinylimidazole)-Na-Bentonite Nanocomposite - ESMER, KADİR (WILEY, 2011)
The adsorption of poly(vinylimidazole) (PVI) onto Na-Bentonite from aqueous solutions has been investigated as a function of temperature. According to the experimental results, the adsorption of PVI decreases with temperature from 25 to 55 degrees C. The study of temperature effect has been quantified by calculating various thermodynamic parameters such as Gibbs free energy, enthalpy and entropy changes. The electrical and dielectrical properties of PVI Na Bentonite composite have been investigated. The current-voltage studies show that conductivity was increased at T = 25 degrees C. The dc conductivity was calculated at T = 25 degrees C. The samples show typical dielectric behavior from capacitive measurements. Depending on maximum interactions at 25 degrees C, ac conductivity and loss factors are also in high values. Especially, at frequencies over 1.5 kHz, it was seen completely clay behavior. Variation of tangent loss factor-frequency shows decreasing of polarization density in structure in high frequency. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 874-879, 2011
Keywords: poly(vinylimidazole); adsorption; Na-Bentonite; electrical conductivity; dielectric properties; ELECTRICAL-CONDUCTIVITY; AC CONDUCTIVITY; CATIONIC POLYACRYLAMIDE; DC CONDUCTIVITY; ADSORPTION; SILICA; CLAY; BENTONITE; WATER; POLYVINYLIMIDAZOLE